John Burns (1856-1943) (1888)
1888 1880-1914 "John Burns (1856-1943)" [T0027.jpg], 1888 John Burns (1858-1943) worked as an engineer in London and Nigeria, West Africa. After his return from Africa in 1881, he joined the Amalgamated Society of Engineers and became increasingly active in socialist politics. In 1884, he joined the Social Democratic Federation (SDF) and unsuccessfully contested Nottingham as a SDF parliamentary candidate in 1885. He served 6 weeks imprisonment after attempting to break a police cordon around Trafalgar Square on Bloody Sunday -13 November 1887- the culmination of the campaign for free speech in Ireland.